2016
DOI: 10.2754/avb201685040371
|View full text |Cite
|
Sign up to set email alerts
|

The influence of feeding purple wheat with higher content of anthocyanins on antioxidant status and selected enzyme activity of animals

Abstract: The influence of anthocyanins on antioxidant activity and liver function was measured in three different animal species (rats, chickens and fish). Purple Konini wheat with the total anthocyanin content (TAC) of 41.70 mg/kg was fed to the experimental groups of animals (rats n = 32; chickens n = 32; fish n = 20). The same numbers of animals (control groups) were fed common wheat with TAC of 24.95 mg/kg. At the end of the experiment, the animals were killed and blood and liver tissues were taken for biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Anthocyanins have several properties in humans and animals, such as anti-inflammatory, antimicrobial, antioxidant activities. They prevent oxidative liver damage and hyperglycemia, prevent cardiovascular diseases and diabetes, improve vision and obesity control [13][14][15]. Moreover, anthocyanins prevent atherosclerosis, reduce free radical activity, and decrease inflammation and aging [16].…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins have several properties in humans and animals, such as anti-inflammatory, antimicrobial, antioxidant activities. They prevent oxidative liver damage and hyperglycemia, prevent cardiovascular diseases and diabetes, improve vision and obesity control [13][14][15]. Moreover, anthocyanins prevent atherosclerosis, reduce free radical activity, and decrease inflammation and aging [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, FRAP has been used to determine antioxidant-capacity changes due to the actions of natural pigments, drugs and other foreign agents (Pohanka et al 2011;Mrkvicova et al 2016 Our own results showed a significant decrease in FRAP values in all the organs examined (liver, heart, and gills) after 10 days of exposure, with no significant changes observed after further 20 and 30 days of exposure (Fig. 1).…”
Section: Discussionmentioning
confidence: 73%
“…However, effects like increased lipid peroxidation in the kidney and modified animal behavior related to anxiety were also observed ( 88 ). Purple (Konini) wheat proved beneficial in improving the liver antioxidant activity and liver function enzyme activities in rats and chickens ( 87 ). However, the effect was not observed in a similar study carried out on fishes; the reason could be that fishes could not metabolize the purple wheat properly ( 87 ).…”
Section: Applications Of Colored Wheat In Healthmentioning
confidence: 99%